Play&Tune: User Feedback in the Development of a Serious Game for Optimizing Hearing Aid Orientation. Issue 1 (January 2021) - Hallewell, Madeline; Patel, Harshada; Salanitri, Davide; Picinali, Lorenzo; Cobb, Sue; Velzen, Jeena; D'Cruz, Mirabelle; Simeone, Luca; Simeone, Mauro
Many hearing aid (HA) users are dissatisfied with HA performance in social situations. One way to improve HA outcomes is training the users to understand how HAs work. Play&Tune was designed to provide this training and to foster autonomy in hearing rehabilitation. We carried out two prototype evaluations and a prerelease evaluation of Play&Tune with 71 HA users, using an interview or online survey. Users gave detailed feedback on their experiences with the app. Most participants enjoyed learning about HAs and expressed a desire for autonomy over their HA settings. Our case study reinforces the importance of user feedback during app development.